Comparative analysis of electronic payment systems - A. A. Kulikova; N. A. Mashkovtseva; A. S. Kulikov (Путеводитель предпринимателя, 2020)
With the improvement of technologies it has become possible to develop online commerce and due to this development, electronic money and electronic payment systems have been emerged. The article presents a general scheme of opportunities of working in the most popular electronic payment systems in Russia, the conditions and methods of identification, and also identifying the latest technologies and the existing level of security in electronic payment systems.